25(OH)D3 improves granulosa cell proliferation and IVF pregnancy outcomes in patients with endometriosis by increasing G2M+S phase cells - Rui Hu; Leilei Li; Lanlan Liang; YuXin Qi; Xiaoling Ma; Yuan Yang (BMC, 2023)
Abstract Background The 25-hydroxyvitamin D3 (25 (OH) D3) is crucial for follicular development. This study aimed to investigate the relationship between the level of 25 (OH) D3 in endometriosis patients, pregnancy outcomes of in vitro fertilization (IVF), and the underlying mechanism. Methods The 25 (OH) D3 levels in serum and follicular Fluid (FF) samples were detected using enzyme-linked immunosorbent assay (ELISA). Clinical features and pregnancy outcomes of endometriosis patients were also compared between the deficient group (< 20 ug/ml) and the adequate group (≥ 20 ug/ml). The effects of 25 (OH) D3 on the proliferation and cell cycle of human ovarian granulosa cells were respectively detected by CCK-8 assay and flow cytometry (FCM). The differentially expressed genes (DEGs) in granulosa cells of endometriosis and tubal infertility patients were screened from GEO database. The effects of 25 (OH) D3 on the expressions of CDKN2D, PPARA, TGFB2 and THBD were determined using quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot. Results The levels of 25 (OH) D3 in serum and FF samples were decreased in endometriosis patients. The deficient group had fewer embryos that can be transferred, lower quality embryos and lower clinical pregnancy rates. Adequate 25 (OH) D3 levels in FF samples was a protective factor for live birth outcome in endometriosis patients. 25 (OH) D3 enhanced the proliferation capacity of granulosa cells (the concentration of 10 nM was the most significant) and increased the proportion of G2M + S phase cells. The expression of CDKN2D was decreased and TGFB2 and THBD were significantly upregulated. Conclusions 25 (OH) D3 deficiency may be associated with poor IVF pregnancy outcomes in endometriosis patients. 25 (OH) D3 promotes ovarian granulosa cell proliferation by promoting the ability of cells to divide, and may accelerate cell cycle progression by up-regulating THBD and down-regulating CDKN2D expression.